Second Tithe and Wine: A Historical and Theological Study of Deuteronomy 14:22-29 - Yohanes Verdianto (Syntax Idea, 2021)
Tithing is God's holy, in recognition that God is the owner and man is the servant. But in Deuteronomy 14:22-29 the fact is found that God's holy tithing can be used to buy everything he wants including intoxicating drinks, and even God ordered that the Israelites eat them together with the priests before God. The purpose of the study was to examine the history of the second tithing and its use in Deuteronomy 14:22-29 to find out the true purpose of God's commandments about spending tithing for whatever is desired, spending tithing on intoxicating beverages, and whether this is the legitimacy of God so that His people can currently consume liquor. Research methods are documentary research methods. This is done by evaluating various historical literature in the discussion of tithing festivals and their use. This researcher will conclude research to answer these questions. First of all, in the Bible there are three types of tithing.